2012
DOI: 10.1371/journal.pone.0048395
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Personal Opinions and Experiences in Compliance with Mass Drug Administration for Lymphatic Filariasis Elimination in Kenya

Abstract: BackgroundThe main strategy adopted for Lymphatic Filariasis (LF) elimination globally is annual mass drug administration (MDA) for 4 to 6 rounds. At least 65% of the population at risk should be treated in each round for LF elimination to occur. In Kenya, MDA using diethylcarbamazine citrate (DEC) and albendazole data shows declining compliance (proportion of eligible populations who receive and swallow the drugs) levels (85%–62.8%). The present study's aim was to determine the role of personal opinions and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
55
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 28 publications
3
55
0
Order By: Relevance
“…Hodges et al, 2012 [23]/Sierra Leone/June 2010–2011Programme evaluation11,824 participants interviewed in the end process evaluation of hard to reach (HTR) sites.(Urban and rural settings)12 districts and 4 large towns from southern, eastern and northern provinces.To identify the challenges to effective mass drug administration implementation for LF and the corrective measures taken.Challenges affecting MDA for implementation included: late country delivery of ivermectin, the availability and motivation of unpaid CHVs, remuneration for CHWs, rapid urbanization and employment seeking population migrations.‘In process’ monitoring ensured modifications of LF MDA were made in a timely manner to ensure effective coverage was finally attained in HTR locations.Community participation and Coverage10. Njomo1 et al, 2012 [24]/Kenya/December 2008Mixed- method studyQuantitative data: 965 household heads or adult representatives. Qualitative data: IDIs with 80 LF patients, 80 opinion leaders and 15 CDDs.…”
Section: Resultsmentioning
confidence: 99%
“…Hodges et al, 2012 [23]/Sierra Leone/June 2010–2011Programme evaluation11,824 participants interviewed in the end process evaluation of hard to reach (HTR) sites.(Urban and rural settings)12 districts and 4 large towns from southern, eastern and northern provinces.To identify the challenges to effective mass drug administration implementation for LF and the corrective measures taken.Challenges affecting MDA for implementation included: late country delivery of ivermectin, the availability and motivation of unpaid CHVs, remuneration for CHWs, rapid urbanization and employment seeking population migrations.‘In process’ monitoring ensured modifications of LF MDA were made in a timely manner to ensure effective coverage was finally attained in HTR locations.Community participation and Coverage10. Njomo1 et al, 2012 [24]/Kenya/December 2008Mixed- method studyQuantitative data: 965 household heads or adult representatives. Qualitative data: IDIs with 80 LF patients, 80 opinion leaders and 15 CDDs.…”
Section: Resultsmentioning
confidence: 99%
“…The CDDs followed by other villagers were the most common sources of MDA information across the three socio-economic strata, while the hospital and radio were less common sources of information in the three areas indicating possible lack of reliability of information from CDDs by majority of those in the high socio-economic strata. Similarly, a study on social mobilization and compliance with MDA in rural Kenya [28] revealed that the health professionals did not play a frontline role in disseminating information on MDA suggesting that the information received by some of the community members may have been inadequate and/or incorrect. CDDs and other villagers are non- health professionals who should not be entirely relied upon to disseminate the information.…”
Section: Discussionmentioning
confidence: 99%
“…in Kenya reported “feeling that the drugs were not necessary,” being absent and thinking that the drugs were meant for only patients with LF as major causes of non-compliance. [13] Weerasooriya et al . reported that use of other medicines, a lack of feeling of the necessity for them and forgetting among reasons of non-compliance in Sri Lanka in 2007.…”
Section: Discussionmentioning
confidence: 99%
“…Experience of side-effects including giddiness, fever, headache, and vomiting influenced compliance in Kenya ( P < 0.001). [13]…”
Section: Discussionmentioning
confidence: 99%